Theorizing Homophobia - Adam, Barry D. (Sexualities, 1998)
A series of contemporary theories that have been used to explain homophobia are assessed. Structural, feminist, comparative, gender panic, queer, and socio-historical theories rely on the premises of a diverse set of scholarly disciplines, and in turn, generate their own objects of analysis, whether `homophobia', `heterosexism', or `heteronormativity'. While the current flourishing of gay and lesbian studies has generated important insights into the workings of homophobia, analyses have also tended to be limited and fragmentary. This paper suggests a study of homophobic projects that combines theoretical tools able to recognize experience, discourse, structure, and history.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Looking queer: body image and identity in lesbian, bisexual, gay, and transgender communities - Atkins, Dawn (Haworth Press, 1998)
Looking Queer: Body Image in Lesbian, Bisexual, Gay, and Transgender Communities contains research, firsthand accounts, poetry, theory, and journalistic essays that address and outline the special needs of sexual minorities when dealing with eating disorders and appearance obsession. Looking Queer will give members of these communities hope, insight, and information into body image issues, helping you to accept and to love your body. In addition, scholars, health care professionals, and body image activists will not only learn about queer experiences and identity and how they affect individuals, but will also understand how some of the issues involved affect society as a whole. Dismantling the myth that body image issues affect only heterosexual women, Looking Queer explores body issues based on gender, race, class, age, and disability. Furthermore, this groundbreaking book attests to the struggles, pain, and triumph of queer people in an open and comprehensive manner. More than 60 contributors provide their knowledge and personal experiences in dealing with body image issues exclusive to the gay and transgender communities, including: exploring and breaking down the categories of gender and sexuality that are found in many body image issues finding ways to heal yourself and your community discovering what it means to “look like a dyke” or to “look gay” fearing fat as a sign of femininity determining what race has to do with the gay ideal discussing the stereotyped ”double negative”–being a fat lesbian learning strategies of resistance to societal ideals critiquing ”the culture of desire” within gay men’s communities that emphasizes looks above everything else Revealing new and complex dimensions to body image issues, Looking Queer not only discusses the struggles and hardships of gay, lesbian, bisexual, and transgendered persons, but looks at the processes that can lead to acceptance of oneself. Written by both men and women, the topics and research in Looking Queer offer insight into the lives of people you can relate to, enabling you to learn from their experiences so you, too, can find joy and happiness in accepting your body.
Section: li, 467 p
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; image corporelle; intersectionnalité; premier cycle; queer; régions géographiques; sciences humaines; soc2014; thématiques; troubles alimentaires; états-unis

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Les éditions du remue-ménage, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Section: 214 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

La domination masculine - Bourdieu, Pierre (Seuil, 1998)
Difficile de remettre en question la domination masculin tellement elle est ancrée dans nos inconscients et accordée à nos attentes. Partant d'une description ethnographique de la société kabyle, Pierre Bourdieu explore les structures symboliques de cet inconscient et rocentrique qui survit chez les hommes et les femmes d'aujourd'hui
Keywords: 1900-1999; approches et analyses; cours; cycles supérieurs; discipline; division sexuelle du travail; europe; fem1000; fem7000; france; lit3220; lit3495; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail

Feminism and ecological communities: an ethic of flourishing - Cuomo, Chris J. (Routledge, 1998)
Feminism and Ecological Communities presents a bold and passionate rethinking of the ecofeminist movement. It is one of the first books to acknowledge the importance of postmodern feminist arguments against ecofeminism whilst persuasively preseenting a strong new case for econolocal feminism. Chris J.Cuomo first traces the emergence of ecofeminism from the ecological and feminist movements before clearly discussing the weaknesses of some ecofeminist positions. Exploring the dualisms of nature/culture and masculing/feminine that are the bulwark of many contemporary ecofeminist positions and questioning traditional traditional feminist analyses of gender and caring, Feminism and Ecological Communities asks whether women are essentially closer to nature than men and how we ought to link the oppression of women, people of colour, and other subjugated groups to the degradation of nature. Chris J.Cuomo addresses these key issues by drawing on recent work in feminist ethics as well as teh work of diverse figures such as Aristotle, John Dewey, Donna Haraway adn Maria Lugones. A fascinating feature of the book is the use of the metaphor of the cyborg to highlight the fluidity of the nature/culture distinction and how this can enrich econfeminist ethics and politics. An outstanding new argument for an ecological feminism that links both theory and practice, Feminism and Ecological Communities bravely redraws the ecofeminist map. It will be essential reading for all those interested in gender studies, environmental studies and philosophy.
Keywords: approches et analyses; com5170; cours; discipline; environnement; philosophie; postmodernisme; premier cycle; sciences humaines; thématiques; écoféminisme

Essentialism vs. social constructionism in the study of human sexuality - DeLamater, John D.; Hyde, Janet Shibley (The Journal of Sex Research, 1998)
According to classical essentialism, there are underlying true forms or essences, there is discontinuity between different forms rather than continuous variation, and these true forms are constant over time. Modern essentialism consists of a belief that certain phenomena are natural, inevitable, and biologically determined. We consider sociobiology, evolutionary psychology, genetic research, brain research, and endocrine research as examples of essentialist approaches, focusing particularly on how these research approaches treat sexual orientation and sexual attraction. Social constructionism, in contrast, rests on the belief that reality is socially constructed and emphasizes language as an important means by which we interpret experience. We briefly review social constructionist research on sexual orientation and sexual attraction. Finally, we review examples of conjoint or interactionist research, uniting biological and social influences. We conclude that, although there may be theories and research that conjoin biological and social influences, there can be no true conjoining of essentialism and social constructionism.
Keywords: approches et analyses; comparaison; construction sociale; cours; discipline; essentialisme; histoire et politique; méthodologie; postmodernisme; premier cycle; sciences humaines; sex2283; sociologie; thématiques

Le projet féministe à l’aube du XXIe siècle : un projet de libération et de solidarité qui fait toujours sens - Descarries, Francine (Cahiers de recherche sociologique, 1998)
En situant les rapports de genre au cœur de leur élaboration conceptuelle et en inscrivant leur transformation comme un enjeu stratégique, les études féministes se sont progressivement imposées dans l'univers des sciences humaines comme une approche critique et comme une problématique du changement. Après une revue des trois grands courants de pensée qui se sont développés au sein et en marge du mouvement féministe au cours des dernières décennies, l'auteure se demande si la pensée féministe, ou plutôt les différents courants de la pensée féministe actuelle sont encore engagés dans ces mêmes fins. Sont-elles encore capables de contribuer au renouvellement des savoirs, de proposer un projet de société original, et d'imaginer les termes d'un nouveau contrat entre les genres ? Sont-elles capables de nourrir une lutte féministe unie, une politique de coalition ouverte à la diversité et à la différence, mais qui ne perd rien de sa cohésion et de sa force de ralliement ? Ces questions servent de pistes thématiques pour la discussion de l'auteur.
https://www.erudit.org/en/journals/crs/2011-n51-crs1517846/1002660ar/
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; approches et analyses; cours; discipline; fem1000; féminisme matérialiste; histoire et politique; justice sociale; militance; mouvements des femmes*; mouvements féministes; occident; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; thématiques

Female masculinity - Halberstam, Jack (J.) (Duke University Press, 1998)
Dans cet ouvrage essentiel de la théorie queer, Jack Halberstam s’attaque au statut protégé de la masculinité masculine et montre que la masculinité féminine lui offre une alternative distincte depuis plus de deux siècles. Démontrant que la masculinité féminine n’est pas une mauvaise imitation de la virilité, mais une mise en scène vivante et dramatique de genres hybrides et minoritaires, Halberstam catalogue la diversité des expressions de genre chez les femmes masculines, depuis les pratiques pré-lesbiennes du XIXe siècle jusqu’aux performances contemporaines des drag kings.
Keywords: amériques; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; queer; régions géographiques; sciences humaines; thématiques; états-unis

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Section: x, 193 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Première publication: 1975 http://journals.openedition.org/cedref/171
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes

À quoi peut servir l'imagination : Olympe de Gouges et la Révolution française - Scott, Joan Wallach (La citoyenne paradoxale : les féministes françaises et les droits de l'homme, 1998)
Analyse d'un autre paradoxe à la française : le modèle républicain fondé sur l'égalité et la liberté de la personne, mise au service de l'exclusion politique des femmes, qui n'ont obtenu le droit de vote qu'en 1944. Ce livre traite de la protestation féministe contre cette prétendue universalité des droits, qui excluait les femmes de la citoyenneté.
Keywords: 1700-1799; citoyenneté; cours; discipline; droits des femmes*; europe; fem1000; france; histoire; histoire et politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques

Only the Literal: The Contradictions of Anti-pornography Feminism - Segal, Lynne (Sexualities, 1998)
Within feminism, battles over pornography have become the wars without end. Despite the controversy it generates, the discourses of anti-pornography feminism have continued to make inroads into legal frameworks, most recently in Canada. This piece surveys the growth and questionable appeal of such feminist campaigning, under the theoretical leadership of Catharine MacKinnon: its rewriting of feminist theory; its parasitic relation to the authoritative, phallocentric discourses of gender and sexuality; its alliance with the most reductive, behaviouristic psychology; its disavowel of fantasy and psychic life; its provocative mirroring of both the style and content of the `pornography' it deplores; its unwavering pursuit of legal remedies which enhance the power of state regulation of sexuality; its threat to subversive expressions of women's sexual agency and repudiation of any possibilities for sexual resignifications.
Keywords: cours; discipline; droits des femmes*; histoire et politique; militance; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

Crise et mutation du dispositif de la différence des sexes : regard sociologique sur l'éclatement de la catégorie sexe - St-Hilaire, Colette (Les limites de l'identité sexuelle, 1998)
Keywords: 1900-1999; 1990-1999; amériques; cours; cycles supérieurs; différence des sexes; discipline; fem1000; fem7000; lit3220; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."–BOOK JACKET.
Section: xvi, 175 pages : illustrations ; 24 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

La construction sociale de l'inégalité des sexes. Des outils et des corps - Tabet, Paola (L'Harmattan, 1998)
Aujourd'hui encore, on pense que des contraintes naturelles liées aux capacités reproductives des femmes déterminent leur place dans la société et contribuent à justifier la division du travail entre les sexes. A partir de données sociologiques, ethnologiques et historiques Paola Tabet s'attache à décrire la construction sociale des contraintes dites naturelles qui assignent leur place aux femmes.
Keywords: 1900-1999; anthropologie; cours; discipline; division sexuelle du travail; europe; fem1000; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes; travail

Histoire comparee de l'homosexualite en Allemagne, en Angleterre et en France dans I'entre-deux guerres - Tarnagne, F. (ACTES DE LA RECHERCHE EN SCIENCES SOCIALES, 1998)
Keywords: 1900-1999; allemagne; angleterre; cours; discipline; entre-deux guerres; europe; france; his4860; histoire; histoire et politique; homosexualité; premier cycle; première guerre mondiale; royaume-uni; régions géographiques; sciences humaines; seconde guerre mondiale; sexualité; sexualités dissidentes; thématiques

L'art de la récupération des médias dans Médias et féminismes: minoritaires sans paroles - Yamani, Myriame el (Médias et féminismes: minoritaires sans paroles, 1998)
Les médias, s'ils informent, ne servent plus à communiquer. C'est pourquoi cet essai veut répondre à une double question : comment et pourquoi les minoritaires, et les femmes en particulier, s'ils prennent parfois la parole dans le champ médiatique en créant leurs propres journaux, ne peuvent pas la garder ? Comment et pourquoi les médias majoritaires ne rendent-ils pas compte de ces points de vue de minoritaires, en particulier lors d'événements qui les concernent ?
Section: 268 p. : ill. ; 22 cm
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; médias; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail social; trs1205